Analisis Kesalahan Berbahasa dalam Surat Dinas di Kantor Desa Kabuno Kecamatan Tabona Kabupaten Pulau Taliabu - Djais, Idwan; Ati, Sarmina; Ode, Rahima (Peneliti.net, 2025)
This study aims to describe the types of language errors in official letters issued by the Kabuno Village Office, Tabona District, Taliabu Island Regency. The focus of the study includes spelling errors, diction errors, and errors in effective sentences. The study employed a qualitative descriptive method, with official letter documents as data sources. Data were collected through documentation techniques and analyzed using data reduction, data presentation, and conclusion drawing. The results indicate that language errors are prevalent in spelling, such as capitalization, punctuation, affixes, abbreviations, and numbers. In terms of diction, non-standard words, inaccurate word choice, and uncommon terms were found. Meanwhile, in terms of sentences, sentences were found to be incoherent, inefficient, illogical, incoherent, and non-parallel. These findings indicate the need to improve village officials' understanding of language rules in writing official letters to ensure effective administrative communication.